On the Value of Flexibility in R&D Projects - Santiago, Leonardo P.; Vakili, Pirooz (Management Science, 2005)
In this paper, we consider whether an increase in uncertainty increases the value of a research and development (R&D) project. We also consider the related question of the impact of increased project uncertainty on the value of management flexibility, defined as the difference in value when the project is managed “actively” versus when it is under “passive” management. These questions have already been formulated in an insightful paper in the literature, where different sources of variability and uncertainty in R&D projects are identified and abandonment and improvement at interim stages are considered as options that provide management flexibility. We follow the same formulation. We derive a set of negative results that are contrary to the results of the above-mentioned paper and a set of positive results that are different from those presented. Our negative results indicate that when the source of variability is development uncertainty or market requirement uncertainty, one cannot make a general statement about the impact of increased uncertainty. In some cases, the value of flexibility (and project value) increases and in others it decreases. On the other hand, if the source of variability is market payoff, we show that increased variability increases either the overall project value or the project option value. If the increased variability of market payoff increases the “passive” value of the project, the overall project value also increases; and if it decreases the “passive” value, the value of flexibility, i.e., the project option value, increases.